2008
DOI: 10.1111/j.1440-1673.2008.01989.x
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic fibroma in humerus

Abstract: Desmoplastic fibroma of the bone is a very rare benign tumour, which may be locally aggressive. We report X-ray radiographic and MRI findings of a case of desmoplastic fibroma of the humerus in a 33-year-old man who presented with a slowly enlarging arm mass over years. Desmoid fibroma should be taken into consideration in case of a low T2 signal in a non-sclerotic fibroosseous lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
3
1
3
Order By: Relevance
“…16,20 Classically, DFs have been described as slow growing and relatively benign. 3,24,28 However, this description is not consistent with the DFs we encountered in our two patients; those tumors caused bony destruction and mediastinal compression leading to hypotension over a relatively short period of time. New genetic studies have shown that DFs have the potential to develop malignant transformation characteristics.…”
contrasting
confidence: 44%
“…16,20 Classically, DFs have been described as slow growing and relatively benign. 3,24,28 However, this description is not consistent with the DFs we encountered in our two patients; those tumors caused bony destruction and mediastinal compression leading to hypotension over a relatively short period of time. New genetic studies have shown that DFs have the potential to develop malignant transformation characteristics.…”
contrasting
confidence: 44%
“…Because DFB has dense collagen tissue, the lesion may have a density equal to or higher than surrounding soft tissues with a CT value of 30-66 Hu. High density re ects the dense connective tissue matrix and relative necellularity of tumor 12 . In this group, six patients had the CT value greater than 45 Hu.…”
Section: Discussionmentioning
confidence: 99%
“…This tumour has been observed infrequently in the diaphysis like the one presented here. Only two previous case reports were there on diaphyseal tumours 3 14. Most patients were younger than 30 years of age 2 10.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature since the report by Bohm et al , noted an additional 28 patients primarily in the form of case reports 4–13. Known to be a lesion from metaphysis, diaphyseal localisation of the tumour is rarely reported 14. We intend to report an unusual presentation site of this rare tumour successfully treated at our institution.…”
Section: Introductionmentioning
confidence: 94%